Pengaruh Fraud Hexagon Model Terhadap Kecurangan Laporan Keuangan Perusahaan Transportasi Dan Logistik - Nuridah, Siti; Sitohang, Rony Marthin; Supraptiningsih, Joelianti Dwi; Sagitarius, Elda; Septiani, Arneta (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study discusses the problem of fraudulent financial reporting in a company that is affected by fraud hexagon. The purpose of this study was to examine the effect of financial targets, financial stability and external pressure as part of the stimulus component for fraudulent financial reporting in Transportation and Logistics companies listed on the IDX in 2017-2021. The population of this study are all Transportation and Logistics companies listed on the IDX in 2017-2021. With the purposive sampling method as the sampling method, a sample of 16 companies from 28 Transportation and Logistics companies was obtained as a population. The data used is financial report data obtained by downloading from www.idx.co.id. The data analysis used is panel data regression analysis and the tests used are the T test, F test, and the coefficient of determination. The results of the study show that financial targets have an effect on fraudulent financial reporting. Financial stability and external pressure have no effect on fraudulent financial reporting. While simultaneously, the stimulus component as measured by the financial target variable, financial stability and external pressure has an effect on fraudulent financial reporting